The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s1678-58782004000100003
|View full text |Cite
|
Sign up to set email alerts
|

Toroidal milling of hardened SAE H13 steel

Abstract: It is estimated that around 65% of the cost of a die or mould is related to the machining processes. Moreover, the literature says that 70% of the time spent in the machining processes of this kind of parts is used in finishing and semi-finishing operations. The high complexity of the machined surfaces makes mandatory the use of ball nose tools, with large overhang, what increases vibration in the process. These problems have to be minimized, since dies and moulds demand a very good surface finish and tight di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…According to Fallböhmer and Scurlock [34], cutting with a tool with a small level of wear may generate lower roughness than cutting with a fresh tool. Diniz et al [35] found similar results in the milling of H13 steel with a toroidal tool in semi-finishing conditions. A possible explanation for these results is that roughness values may be associated with tool coating defects on the cutting edge, as cited by Oliveira [13], which affect roughness at the beginning of tool life.…”
Section: Introductionmentioning
confidence: 63%
“…According to Fallböhmer and Scurlock [34], cutting with a tool with a small level of wear may generate lower roughness than cutting with a fresh tool. Diniz et al [35] found similar results in the milling of H13 steel with a toroidal tool in semi-finishing conditions. A possible explanation for these results is that roughness values may be associated with tool coating defects on the cutting edge, as cited by Oliveira [13], which affect roughness at the beginning of tool life.…”
Section: Introductionmentioning
confidence: 63%
“…Under the optimized cutting conditions, the surface roughness was less than 0.25 µm. Diniz et al [4] achieved about 0.8 µm surface roughness value in the toroidal milling of hardened SAE H13. Karkalos et al [30] obtained 0.19 µm surface roughness value when milling Ti-6Al-4V ELI alloy.…”
Section: Optimization For Ramentioning
confidence: 99%
“…The result of their research indicates that the surface roughness under the optimized cutting parameters is less 0.25 µm. Diniz et al [4] studied the toroidal milling of hardened SAE (Society of Automotive Engineers) H13 alloy steel using the minimum quantity of lubricant (MQL) technique. Their result indicates that the surface roughness value is 0.8 µm.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, molds and dies industry present important impact in the competitiveness of the forming processes. In a mold manufacturing it is estimated that 65% of the costs are due to finishing and semi-finishing processes by machining [2,3]. Between these processes, hole-making spends from 25% to 50% of the cycle time and 33% of the total number of operations, requesting reliability due to the high added value to the part being processed [4,5].…”
mentioning
confidence: 99%